Efeitos do tratamento com niacina protegida e levedura rica em cromo em vacas holandesas submetidas à estresse térmico - Aires, Adelina Rodrigues (2012)
Dairy cows subjected to hot environments have considerable production losses. The use of chromium and niacin nutritional options are used with satisfactory effects to improve performance in these situations. However, in the form of chromium yeast and chromium-niacin as protected have not been used together in animals subjected to heat stress, which is the purpose of this study. The production parameters, and metabolic behavior of dairy cows subjected to heat stress were evaluated. We used 46 lactating Holstein cows were kept in breeding system free stall, during the days February 2 to March 11, 2011. The animals were divided into four treatments: protected niacin (GN), yeast rich in chromium (GCr), niacin + chromium (GNCr) and control (GC). Milk production was recorded daily. Blood samples were collected on days zero, 12, 26 and 37 for determination of non-esterified fatty acids (NEFA), β-hydroxybutyrate (BHB), glucose, cholesterol, insulin, cortisol, tetraiodothyronine (T4) and triiodothyronine (T3). Milk samples were collected on days zero, 7, 28 and 35 for somatic cell count (SCC) and determination of milk urea nitrogen (MUN). The ingestive behavior of water consumption, rumination and idleness were seen once a week for 24 hours. The use of more chromium niacin increased milk production compared to isolated use of these supplements. The GCr had the lowest value of BHB, while GN had the highest value. The GN had higher cholesterol levels than the group GNCr. There were also differences in the groups GN and GCr and the values of T3, and GN showed the highest levels. The somatic cell count (SCC) was lower in animals supplemented with niacin (GNCr and NG). The MUN was higher in the groups receiving niacin compared to the group that received only chromium. The animals that received niacin, remained lying down more frequently compared to the control group, between 13 and 18 h. In the interval from 19 to 24 h water intake was higher for animals receiving niacin and higher rumination activity in animals receiving chromium. The use of chromium + niacin has a positive effect on milk production, as well as the reduction of SCC in animals submitted to heat stress. The 7% increase in milk production generated by the administration of niacin + chromium in the production presents an alternative for producers who need to maintain the production of his flock during periods of hot weather.